Penggunaan Buku Interaktif BUMJA dalam Meningkatkan Keterampilan Menulis Arab Untuk Anak Usia Sekolah Dasar - Zakia Eka Putri; Mualifatul Hasanah; Silvia Sri Rahayu; Ani Nur Aeni (Publikasi Indonesia, 2022)
An introduction to reading and writing the Qur'an is a must given to elementary school-aged children who are Muslim. Al-Qur'an is the holy book of Muslims which acts as a source of law and basic knowledge that is used as a benchmark for shaping children's behavior. By learning the basics of the Qur'an such as reading and writing, children can recognize the good values ​​contained in the Qur'an. Through learning the Qur'an can shape the religious character of children, one of which is being able to read and write it. This research was conducted to find out how good learning to write the Qur'an is for elementary school-aged children. The method used for this research is descriptive qualitative. Data collection techniques in this study were carried out by interviewing elementary school-aged children as well as articles and research results that had been carried out by previous researchers. The analyzed data is relevant to the research and the findings from several references describe how to learn to write the Qur'an for elementary school-aged children.